2011
DOI: 10.1063/1.3553414
|View full text |Cite
|
Sign up to set email alerts
|

Tuning exchange bias in ferromagnetic/ferromagnetic/antiferromagnetic heterostructures [Pt/Co]/NiFe/NiO with in-plane and out-of-plane easy axes

Abstract: In-plane exchange bias (EB) in [Pt/Co]n/NiFe/NiO heterostructures with orthogonal easy axes is investigated. The reversible in-plane EB effect at the ferromagnetic (FM)/FM [Pt/Co]n/NiFe interface allows one to manipulate the value and direction of the EB of the heterostructures, which can be induced by applying a magnetic field larger than the perpendicular anisotropy field of the [Pt/Co]n multilayers. The difference between the EB of the heterostructures after field cooling and zero field cooling disappears a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…12 Ag(10 nm)/Co(t Co )/NiO(5 nm)/Ag(5 nm) antidot arrays on AAO templates and the corresponding sheet films on Si and Al 2 O 3 substrates were prepared by means of using DC and RF magnetron sputtering of Ag, Co, NiO targets with 99.99% purity. 13 The base pressure was better than 3 Â 10 À7 Torr and the Ar pressure during deposition was 4 Â 10 À3 Torr. The morphological characterization was carried out with high-resolution scanning electron microscopy (SEM) and Tecnai G 2 F20 transmission electron microscopy (TEM).…”
mentioning
confidence: 97%
“…12 Ag(10 nm)/Co(t Co )/NiO(5 nm)/Ag(5 nm) antidot arrays on AAO templates and the corresponding sheet films on Si and Al 2 O 3 substrates were prepared by means of using DC and RF magnetron sputtering of Ag, Co, NiO targets with 99.99% purity. 13 The base pressure was better than 3 Â 10 À7 Torr and the Ar pressure during deposition was 4 Â 10 À3 Torr. The morphological characterization was carried out with high-resolution scanning electron microscopy (SEM) and Tecnai G 2 F20 transmission electron microscopy (TEM).…”
mentioning
confidence: 97%
“…Previous theoretical and experimental researches found that the EB field H E p1/(t FM ) m which is ascribed to negligible FM anisotropy and strong coupling at the FM/AFM interface [18][19][20][21][22]. On the other hand, EB is strongly determined by the anisotropy constant and t AF of AFM layer [23,24].…”
Section: Introductionmentioning
confidence: 94%
“…It can be used as a pinned ferromagnetic layer in an FM/antiferromagnetic (AFM) exchange-biasing system, including NiFe/IrMn, NiFe/NiO, and NiFe/PtMn systems [4][5][6]. In particular, an NiFe thin film can be inserted to a pinned or free layer of magnetic tunnel junctions (MTJs) in magnetoresistance random access memory (MRAM) and recording-head applications [7,8].…”
Section: Introductionmentioning
confidence: 99%